MITIGATING THE PRINCIPLE OF SOVEREIGNTY OVER BIOLOGICAL RESOURCES? - Oliveira, Liziane Paixão Silva; Barros -Platiau, Ana Flávia; Gomes do Cravo Barros, Jorge (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2018)
With time, States' sovereign rights were limited by international law and the western liberal order under the UN auspices. Concerning environmental issues, the Convention on Biological Diversity (CBD) stressed this trend within national jurisdiction. However, concerning resources beyond national jurisdiction, legal doctrine and international relations theories offered a heated debate on the validity of the principle of sovereignty over biological resources. It is the case for the Antarctic Treaty System and the biodiversity beyond national jurisdiction regime (BBNJ). Therefore, there is a clear and partial fragmentation of the international environmental legal system, due to the limited circulation of principles. For some authors, the common concern of mankind represents a threat to this principle, while for others sovereignty is still totally assured by legal commitments. After an analysis of the UN resolutions, we discuss sovereign rights and the CBD, and then we look at the common concern of mankind. From a legal and political standpoint, the results are that the principle of sovereignty had a double-fold evolution: it is limited by the concept of common interest of mankind and the international obligations more than ever, but it is not challenged by them.